Planning Approach to Organisational and Methodical Provision of Formation and Functioning of Logistic Systems of Enterprises - Kolodizyeva Tetyana O.; Panasyants Hanna S. (Bìznes Inform, 2013)
The article analyses factors of external and internal environment of enterprises that influence the process of formation of logistic systems and justifies expediency of use of the planning approach to development of the organisational and methodical provision of functioning of logistic systems of enterprises. The article offers to conduct development of organisational and methodical provision of formation of functioning of logistic systems with the use of not one but several methodological approaches: situational, process, functional and planning. The conducted analysis allowed composing a basic project, which could be laid in the foundation of formation of a logistic system by any enterprise for meeting requirements of the planning triangle: content / borders, time, cost, taking into consideration the forth limitation – quality.